2021
DOI: 10.55563/clinexprheumatol/sd1exj
|View full text |Cite
|
Sign up to set email alerts
|

A multi-predictor model to predict risk of scleroderma renal crisis in systemic sclerosis: a multicentre, retrospective, cohort study

Abstract: Objective. Scleroderma renal crisis (SRC) is a life-threatening syndrome. The early identification of patients at risk is essential for timely treatment to improve the outcome. Therefore, it is of great interest to provide a personalised tool to predict risk of SRC in systemic sclerosis (SSc). Methods. We tried to set up a SRC prediction model based on the PKUPH-SSc cohort of 302 SSc patients. The least absolute shrinkage and selection operator (Lasso) regression was used to optimise disease features. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Several researchers have reported that the hemoglobin level was an independent risk factor for 3-to-5-year mortality in early dcSSc patients [ 36 ], in-hospital mortality [ 37 ], severe skin thickness [ 38 ], as well as higher healthcare costs related to organ damage [ 39 ] in SSc patients. In addition, patients with anemia also showed a more significant progression of organ damage during follow-up, which has been reported in our previous cohort study [ 20 ], and shows that anemia was a predictor for the renal involvement of SSc. In our results, baseline anemia was related to the progression of organ damage in the high-burden SCTC-DI group among lcSSc and dcSSc patients and in the low-burden SCTC-DI group of SSc patients with overlap syndrome.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several researchers have reported that the hemoglobin level was an independent risk factor for 3-to-5-year mortality in early dcSSc patients [ 36 ], in-hospital mortality [ 37 ], severe skin thickness [ 38 ], as well as higher healthcare costs related to organ damage [ 39 ] in SSc patients. In addition, patients with anemia also showed a more significant progression of organ damage during follow-up, which has been reported in our previous cohort study [ 20 ], and shows that anemia was a predictor for the renal involvement of SSc. In our results, baseline anemia was related to the progression of organ damage in the high-burden SCTC-DI group among lcSSc and dcSSc patients and in the low-burden SCTC-DI group of SSc patients with overlap syndrome.…”
Section: Discussionsupporting
confidence: 85%
“…We retrospectively identified two cohorts of patients who were diagnosed as SSc at the Department of Rheumatology and Immunology of Peking University Third Hospital (PKUTH) and Peking University People’s Hospital (PKUPH) from January 2001 to July 2021, as reported previously [ 20 ]. The Ethics Committee approved the study of Peking University Third Hospital ((2022) 142-01)) and Peking University People’s Hospital (2019PHB276-01).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we should remain vigilant for MI in patients with positivity to anti-SCL70 antibody and wide skin sclerosis. The correlation between scleroderma renal crisis (SRC) and cardiac or myocardial involvement has been reported in previous studies [21,22]; severe myocardial damage resulted in reduced blood supply to the kidneys, thus aggravating renal ischemia.…”
Section: Discussionmentioning
confidence: 85%
“…Managing autoimmune hepatitis is difficult with diffuse cutaneous SSc patients, as these patients may develop a renal crisis with high-dose steroid therapy [ 19 , 20 ]. Future studies are required to determine the treatment outcome and complications of high-dose steroid therapy for combined autoimmune hepatitis and SSc.…”
Section: Discussionmentioning
confidence: 99%